Editorial - González-Campo, Carlos Hernán (Cuadernos de Administración, 2017)
In this editorial of the 57th issue, volume 33 of our Journal Cuadernos de Administración, I want to present the new changes that we face in this editorial project that is on its 40th year of publication. The first great change is to start publishing our Journal in English, seeking a greater diffusion of knowledge from different authors. The second change is to publish three issues per year. 2017 is the first year when we will publish three issues. Finally, the third great change is to become a 100% electronic Journal. We are seeking a greater diffusion and availability. Now the task that we will be facing is to be included in the largest number of data bases and to make our data increasingly open to accomplish a greater amount of downloads of articles.